NEMATODA ENTOMOPATOGEN INDIGENOUS DALAM UJI PERBANDINGAN EFIKASI PENGENDALIAN Plutella xylostella (Lepidoptera: Plutellidae) - Febrianasari, Ria; Azizah, Maziatul Umi; Damayanti, Annike Putri; Arif Zulfahmi, Muhamad Guruh (Program Kreativitas Mahasiswa - Penelitian, 2014)
The problems in cultivated cabbage is cabbage caterpillar (Plutella xylostella). Attack of P. xylostella can result in a loss of 100% yield. Entomopathogenic nematode (EPNs) are parasite nematode that attack specific insect larvae but is safe for animals and plants and has great opportunity for becoming pest control such as P. xylostella. The objective of this research was to compare the EPNs with synthetic pesticide to control P. xylostella. The research was conducted in Pandesari village, Pujon subdistrict, Malang district started on February until May 2014. The research used single-factor group of a randomized design with six treatments and four replications, designated as control (without treatment), EPNs 200 J1/ml, EPNs 400 J1/ml, EPNs 800 J1/ml, two pesticides with active ingredients klorpirifos and spinosad. Effectivity of insecticide (EI) from data were calculated with Abbot formula. Treatments that showed value greater than 70% was categorized as effective against target pest. The treatments gave significant effect to larvae population and damage percent incident variable. The result showed that EPNs was isolated from soil isolation in high populations (22.185 J1/ 0,25 ml). High doses give high control effectiveness and EPNs 800 J1/ml give best control effectiveness (78,36%). Keywords: Plutella xylostella, Entomopathogenic nematode,